Alfred Adler's View of Superiority in Overcoming Stagnation of Learning Motivation Among Students - Pratama, Nurfigita; Z, Sri Putri Rahayu; Lena, Roy (Darussalam: Journal of Psychology and Educational, 2023)
Motivation to study among students is a very crucial matter, it is often encountered by students who prefer to stop studying for various reasons that lead to a lack or loss of motivation in taking lectures. It can be understood that they do not have or may not even have an achievement or a goal for them to realize. This paper aims to examine Alfred Adler's view of superiority in overcoming the stagnation of learning motivation among students. This study uses a type of library research by obtaining data by collecting data through secondary data sources, be it from books, journals, or related sources. Superiority or success in the final comes from individual fighting power. Even though in the process of achieving success, fighting power is an innate aspect of the individual, but in its application the individual must develop this potential in his own way, with goals or objectives that will make direction and guidance to obtain superiority. This view is expected to be able to provide solutions for students to be able to feel more empowered in fulfilling learning motivation to achieve an achievement or goals in their life.